Analysis of Digital and Interpersonal Competence, Organizational Climate on Employee Performance with Motivation Mediation at UPT PLN Malang - Dwi Danesty Deccasari; Marli (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the influence of digital competence, interpersonal competence, and organizational climate on employee performance with work motivation as a mediating variable at the PLN Malang Technical Implementation Unit (UPT PLN Malang). A quantitative approach with SEM-PLS was applied to 98 employees selected through saturated sampling. The results show that digital competence, interpersonal competence, and organizational climate have a positive and significant effect on work motivation; digital competence, interpersonal competence, and work motivation significantly affect employee performance; organizational climate has no significant direct effect on performance; and work motivation mediates these relationships.